Performance-based seismic design of flexible-base multi-storey buildings considering soil–structure interaction - Lu, Yang; Hajirasouliha, Iman; Marshall, Alec M. (Elsevier, 2016)
A comprehensive parametric study has been carried out to investigate the seismic performance of multi-storey shear buildings considering soil–structure interaction (SSI). More than 40,000 SDOF and MDOF models are designed based on different lateral seismic load patterns and target ductility demands to represent a wide range of building structures constructed on shallow foundations. The cone model is adopted to simulate the dynamic behaviour of an elastic homogeneous soil half-space. 1, 5, 10, 15 and 20-storey SSI systems are subjected to three sets of synthetic spectrum-compatible earthquakes corresponding to different soil classes, and the effects of soil stiffness, design lateral load pattern, fundamental period, number of storeys, structure slenderness ratio and site condition are investigated. The results indicate that, in general, SSI can reduce (up to 60%) the strength and ductility demands of multi-storey buildings, especially those with small slenderness ratio and low ductility demands. It is shown that code-specified design lateral load patterns are more suitable for long period flexible-base structures; whereas a trapezoidal design lateral-load pattern can provide the best solution for short period flexible-base structures. Based on the results of this study, a new design factor RF is introduced which is able to capture the reduction of strength of single-degree-of-freedom structures due to the combination of SSI and structural yielding. To take into account multi-degree-of-freedom effects in SSI systems, a new site and interaction-dependent modification factor RM is also proposed. The RF and RM factors are integrated into a novel performance-based design method for site and interaction-dependent seismic design of flexible-base structures. The adequacy of the proposed method is demonstrated through several practical design examples.